ANALISIS BUTIR SOAL UJIAN SEMESTER MATA PELAJARAN KIMIA KELAS X MADRASAH ALIYAH DI KECAMATAN PASIR PENYU - Putri Sakinah; Pangoloan Soleman Ritonga (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
AbstractThis research is motivated by the exam questions in the odd semester of 2015/2016 of which items have not been analyzed. Furthermore, the test result of the odd semester is under the minimum completion criteria. This document analysis research is aimed at discovering the quality of question items qualitatively and quantitatively. The result of the study suggests that 40 items of the odd semester chemistry subject exam questions are not qualitatively compliance with all material aspects, constructions, and the language examined from class 10 of Islamic Senior High School Ponpes Khairul Ummah. Furthermore, at MA Nurul Falah, there are 19 items which are not compliance with the aspect of materials, constructions, and the language that is examined. Quantitatively, there are 29 valid items at MA Ponpes Khairul Ummah and possess test reliability as many as 0.65. At MA Nurul Falah there are 31 valid items and possess test reliability as much as 0.76. Keywords: Analysis of grain problem, chemistry, qualitative, quantitative